Facial mask disturbs ocular exploration but not pupil reactivity - Rabadan, Vivien; Ricou, Camille; Latinus, Marianne; Aguillon-Hernandez, Nadia; Wardak, Claire (Frontiers in Neuroscience, 2022)
Introduction The COVID-19 pandemic has imposed to wear a face mask that may have negative consequences for social interactions despite its health benefits. A lot of recent studies focused on emotion recognition of masked faces, as the mouth is, with the eyes, essential to convey emotional content. However, none have studied neurobehavioral and neurophysiological markers of masked faces perception, such as ocular exploration and pupil reactivity. The purpose of this eye tracking study was to quantify how wearing a facial accessory, and in particular a face mask, affected the ocular and pupillary response to a face, emotional or not. Methods We used videos of actors wearing a facial accessory to characterize the visual exploration and pupillary response in several occlusion (no accessory, sunglasses, scarf, and mask) and emotional conditions (neutral, happy, and sad) in a population of 44 adults. Results We showed that ocular exploration differed for face covered with an accessory, and in particular a mask, compared to the classical visual scanning pattern of a non-covered face. The covered areas of the face were less explored. Pupil reactivity seemed only slightly affected by the mask, while its sensitivity to emotions was observed even in the presence of a facial accessory. Discussion These results suggest a mixed impact of the mask on attentional capture and physiological adjustment, which does not seem to be reconcilable with its strong effect on behavioral emotional recognition previously described.